Cephalometric and malocclusion analysis of Kadazan Dusun ethnic orthodontic patients - Rohaya Megat Abdul Wahab Hartini Idris; Habibah Yacob; Shahrul Hisham Zainal Ariffin (Universiti Kebangsaan Malaysia, 2013)
The aims of this study were to assess the skeletal pattern and the malocclusion of Kadazan Dusun ethnic patients who seek for orthodontic treatment. Cephalometric radiographs (248) and 345 study models were collected from four orthodontic clinics in Sabah. The cephalometric mean values (SNA, SNB, ANB, MMA, SNMxP, UIMxP, LIMnP and ALFH) were measured and the study models were analysed for overjet, overbite, incisor and molar relationships. Some morphological or occlusal features such as shovel shape, Talon cusp, peg shape teeth, midline diastema, canine displacement and supernumerary tooth were also noted. The frequency and correlation of cephalometric mean values and prevalence of malocclusion were analysed using SPSS 18. Class I Skeletal pattern was the most common (48%) followed by Class II (33%) and Class III (18%). There was a strong correlation between SNA and SNB values (>0.70). Class II/1 incisor relationship has the highest frequency (41%) followed by Class III (32%), Class I (21%) and Class II/2 (6%). Class II Molar relationship of both right and left showed highest frequency (38%) followed by Class I (33%) and Class III (30%). Increased of overjet (44%) and reduced overbite (41%) and shovel-shaped incisor were the most common occlusal and dental features. The Kadazan Dusun patients who seek for orthodontic treatment in Sabah were mostly presented with Class I Skeletal pattern with high prevalence in Class II/1 incisor relationship, Class II molar relationship, increased overjet and reduced overbite. The orthodontic treatment pertaining to this ethnicity should be in line with the findings that will benefit patient specifically based on their common presented features.